Knowledge Transfer Program: Early detection of Mild Cognitive Impairment and Prevention of Dementia - Shalihin, Mohd Shaiful Ehsan; Wan Mamat, Wan Hasliza; Mohamad Zahir, Mohd Zulkifli; Mohammad Aidid, Edre (2021)
This slide presentation consists of the introductory part and flow of the program of Early detection of Mild Cognitive Impairment and Prevention of Dementia in Rumah Ehsan, Dungun, Terengganu.